The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages in any new schemes which may be started. A group already organised before it enters the scheme will have a much greater influence than the same number of individuals entering the scheme unorganised. There should of course be no discrimination against any youth organisation on ideological grounds provided it accepts the discipline necessary to the new scheme and loyally adheres to it. 4. Care of the Aged. Hitherto the inadequacy of the provision for the aged has been one of the worst blots on our national record. Apart from the niggardly old age pension practically nothing has been done to make the life of old people worth living, except by a few charitable foundations, who have provided almshouses. It has been assumed that sons and daughters would provide homes for aged parents, but the means test does not encourage this. Old people who have no relatives, or who do not wish to live with their relatives, are condemned to a life of lonely poverty, the only alternative to living alone being the disgrace and dreariness of the "Institution." For the infirm aged there is nothing but the chronic ward, usually situated in the dingiest and oldest of municipal hospitals. No provision for evacuating or rehousing old people was made before the blitz and the blitz uncovered their misery. Many were found living 10 15X/2/464/1